Changes in quality of life and exercise capacity following initiation of supplemental oxygen in patients with idiopathic pulmonary fibrosis - Laurie D Snyder; Daniel M Wojdyla; Megan L Neely; Jad Kebbe; Vinicius C Antao; Divya C Patel (BMC Pulmonary Medicine, 2026)
Abstract Background In patients with idiopathic pulmonary fibrosis (IPF), supplemental oxygen may improve symptoms but may also place a burden on patients. We investigated changes in quality of life and exercise capacity following initiation of supplemental oxygen, and associations between initiating oxygen and clinical outcomes, in patients with IPF. Methods We used data from the IPF-PRO Registry to evaluate changes in St. George’s Respiratory Questionnaire (SGRQ) total and domain scores, Cough and Sputum Assessment Questionnaire (CASA-Q) cough impact and symptoms domain scores and 6-minute walk test distance (6MWD) in patients with IPF before and after initiation of oxygen using linear regression (adjusted for lung function before oxygen initiation). We evaluated associations between initiation of oxygen and risk of clinical outcomes using Cox models. Results Among 611 patients, 343 (56.1%) initiated oxygen with activity and 245 (40.1%) initiated oxygen with activity and at rest (median follow-up: 51.5 months). There were significant mean increases (worsenings) in SGRQ total, activity and impact scores of 5.7, 7.3, and 5.1, respectively, after initiation of oxygen with activity, and in SGRQ total, activity, impact and symptoms scores of 8.6, 9.5, 8.2, and 6.9, respectively, after initiation of oxygen with activity and at rest. There was a significant mean decrease (worsening) in CASA-Q cough impact score of 6.4 after initiation of oxygen with activity and at rest. There were non-significant decreases in 6MWD (m) of 41.0 and 52.4, respectively, after initiation of oxygen with activity and initiation of oxygen with activity and at rest. Risks of subsequent respiratory hospitalization, death or lung transplant, and death were significantly greater among patients who did versus did not initiate oxygen. Conclusions Among patients with IPF, worsening of quality of life and exercise capacity were observed following initiation of supplemental oxygen. Clinical outcomes were worse in patients using than not using oxygen. These data provide further evidence that initiation of supplemental oxygen is a milestone in the patient journey in IPF, but should not be interpreted as showing that initiation of oxygen in itself has deleterious effects. Clinical trial number ClinicalTrials.gov (NCT01915511). Registered on 1 August 2013.